Antioxidant activity evaluation and HPLC‐photodiode array/MS polyphenols analysis of pomegranate juice from selected italian cultivars: A comparative study. Issue 13 (23rd February 2016) - Fanali, Chiara; Belluomo, Maria Giovanna; Cirilli, Marco; Cristofori, Valerio; Zecchini, Maurizio; Cacciola, Francesco; Russo, Marina; Muleo, Rosario; Dugo, Laura
Abstract : Chemical composition of pomegranate juice can vary due to cultivar, area of cultivation, ripening, climate, and other variables. This study investigates the polyphenolic composition and antioxidant activity of juices obtained from six old Italian pomegranate cultivars. Fruit accessions physicochemical characteristics were determined. Total polyphenols content (TPC), anthocyanin content (TAC) and proanthocyanidin content (TPAC) were measured in the juice samples. Phenolic bioactive molecules were analyzed by HPLC‐photodiode array (PDA)/ESI‐MS in all the pomegranate juices. In total, seven nonanthocyanidinic and six anthocyanidinic compounds were identified. The six anthocyanins were found in all juices although at different amounts. These results were correlated with antioxidant activity measured by three different chemical assays: 2, 2 diphenyl‐1‐picrylhydrazyl (DPPH ) scavenging activity assay, Trolox equivalent antioxidant capacity (TEAC) method and ferric reducing‐antioxidant power (FRAP) assay. Pomegranate juices obtained by six different varieties show variable polyphenolic content and antioxidant activity. The antioxidant capacity methods used have shown variable sensitivity, supporting the hypothesis that different methods for the assessment of antioxidant capacity of food compounds are indeed necessary, due to complexity of sample composition and assay chemical mechanism and sensitivity. Juices from Italian pomegranate show good levels of polyphenols content and antioxidant activity making them potential candidates for employment in the food industry.